METHOD FOR ESTIMATING THE DOPPLER FACTOR OF A BROADBAND SIGNAL UNDER CONDITIONS OF MULTIPLICATIVE INTERFERENCE WITH UNKNOWN PROBABILITY DISTRIBUTION - Pavlo Kostenko; Mykyta Alonkyn; Valeriy Slobodyanuk; Mykhailo Rovetskii; Ivan Rovetskii (Електроніка та інформаційні технології)
Background. The paper presented a method for estimating the Doppler factor of a received broadband pulse signal distorted by multiplicative interference with an a priori uncertain probability distribution. This paper was considered a case where the multiplicative interference in the observation has a Gaussian distribution Special attention is paid to the logistic distribution of interference, which is characterized by "heavier tails" of the probability density distribution.